Pravastatin in preeclampsia: A meta-analysis and systematic review - Mészáros, Balázs; Veres, Dániel Sándor; Nagyistók, Luca; Somogyi, Anikó; Rosta, Klára; Herold, Zoltán; Kukor, Zoltán; Valent, Sándor (Frontiers in Medicine, 2023)
Objective Systematic review of the efficacy and safety of pravastatin use in preeclampsia (both in prophylactic therapy and treatment purposes) and meta-analysis of pravastatin use in the prevention of preeclampsia Design Systematic review and meta-analysis of former clinical studies with pravastatin use in preeclampsia. Data collection Two independent reviewers collected data from the PubMed, Scopus, Web of Science, clinicaltrials.gov database of studies published between 2003 and 2022. Results The authors extracted data from the mentioned online database using the keywords of ‘pravastatin; statin; preeclampsia; pre-eclampsia’; and they selected to review fourteen articles. In these studies, altogether 797 women received pravastatin during their pregnancy and 773 women received placebo, thus summarizing the effects of pravastatin use: the possible benefits and adverse effects. Five articles were selected for a meta-analysis on preventing preeclampsia, all these studies started to treat preeclamptic women before the 20th gestational weeks. Pravastatin treatment reduced the incidence of preeclampsia by 61% and premature birth by 45%. Among the newborns, there was a 45% reduction in intrauterine growth retardation (IUGR) in the treated group, as well as a 77% reduction in those receiving neonatal intensive care units (NICU) admissions. Conclusion Our research indicates that pravastatin has a positive effect on women at risk of preeclampsia in the prevention of the disorder. We also found that pravastatin has a positive effect on neonates: pravastatin lowers the incidence of IUGR, the relative risk of premature delivery and decreases the number of NICU admissions among newborns.